(untitled) (Research, Society and Development, 2022)
The use of medicinal plants has been part of human history for many decades, however, this culture, which was somewhat forgotten until then, has been gaining ground again. -analyses of insomnia. For the descriptor terms, the following are cited: Insomnia, herbal medicine and meta-analysis, with an emphasis on reviews aimed at insomnia therapy. Thirty-four review articles were found, two were eliminated after reading the abstract and 31 did not speak directly about insomnia and its cure with medicinal plants and only one surveyed the cure for insomnia with plants through aromatherapy. With the help of the meta-analysis technique in the study used, they observed that aromatherapy is efficient in the treatment of insomnia. They carried out a survey of 417 articles, where at the end of the research they used the responses of 19 articles from 2014 to 2020. Insomnia is prevalent in the Brazilian population and the use of medicinal plants, with sedative activity, stands out among the treatments.